Physicochemical characterization of in situ drug-polymer nanocomplex formed between zwitterionic drug and ionomeric material in aqueous solution (2017)
Biocompatible polymeric materials with the potential to form functional structures, in association with different therapeutic molecules, in physiological media, represent a great potential for biological and pharmaceutical applications. Therefore, here the formation of a nano-complex between a synthetic cationic polymer and model drug (ampicillin trihydrate) was studied. The formed complex was characterized by size and zeta potential measurements, using dynamic light scattering and capillary electrophoresis. Moreover, the chemical and thermodynamically stability of these complexes were studied. The ionomeric material, here referred as EuCl, was obtained by equimolar reaction between Eudragit E and HCl. The structural characterization was carried out by potentiometric titration, FTIR spectroscopy, and DSC. The effect of pH, time, polymer concentration and ampicillin/polymer molar ratio over the hydrodynamic diameter and zeta potential were established